Theoretical and experimental analysis of 1.3-μm InGaAsN/GaAs lasers - Choulis, Stelios A.; Tomić, Stanko S.; O'Reilly, Eoin P O (My University, 2003)
We present a comprehensive theoretical and experimental analysis of 1.3-μm InGaAsN/GaAs lasers. After introducing the 10-band k · p Hamiltonian which predicts transition energies observed experimentally, we employ it to investigate laser properties of ideal and real InGaAsN/GaAs laser devices. Our calculations show that the addition of N reduces the peak gain and differential gain at fixed carrier density, although the gain saturation value and the peak gain as a function of radiative current density are largely unchanged due to the incorporation of N. The gain characteristics are optimized by including the minimum amount of nitrogen necessary to prevent strain relaxation at the given well thickness. The measured spontaneous emission and gain characteristics of real devices are well described by the theoretical model. Our analysis shows that the threshold current is dominated by nonradiative, defect-related recombination. Elimination of these losses would enable laser characteristics comparable with the best InGaAsP/InP-based lasers with the added advantages provided by the GaAs system that are important for vertical integration
Keywords: Semiconductor lasers; Gallium arsenide; Laser transitions; Nitrogen; Optical fibers